Taxonomi Pendidikan Dimensi Pengetahuan, Sikap, dan Keterampilan - Huseng, Andi Maggalatung; Auliyauddin, Shoif; N, Nursalam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper examines how educational taxonomy can be used as a reference in developing three important aspects in students, so that holistic national education goals can be achieved optimally. In this paper, the author uses a descriptive qualitative method with the main data source from library data. Furthermore, the collected data is coded, reduced and conclusions are drawn according to the needs of the research data. The results of the study indicate that Bloom’s Taxonomy is a conceptual framework developed to classify educational goals into systematic categories. This concept was first introduced by Benjamin S. Bloom with a group of education experts in 1956. This taxonomy aims to provide guidance to educators in designing, implementing, and evaluating the learning process in a more focused and measurable manner. In addition, the domain of knowledge (cognitive) in Taxonomy is related to memory, thinking and reasoning processes. The domain of knowledge includes two dimensions, namely (1) cognitive processes, and (2) types of knowledge.